Enhanced sialyltransferases transcription in cervical intraepithelial neoplasia. - López-Morales, Dolores; Velázquez-Márquez, Noé; Valenzuela, Olivia; Santos-López, Gerardo; Reyes-Leyva, Julio; Vallejo-Ruiz, Verónica (Investigación Clínica, 2009)
Altered sialylation observed during oncogenic transformation, tumor metastases and invasion, has been associated with enhanced sialyltransferases (STs) transcription. Increased mRNA expression of STs (ST6Gal I, ST3Gal III) has been detected in invasive cervical squamous cell carcinoma. A study of the sialic acid concentration in local tissue of cervix and in serum showed a slight elevation in benign inflammatory lesions and a moderate elevation in severe neoplasia, but to date, altered expression of STs in cervical intraepithelial neoplasia has not yet been evaluated. This study investigates the changes in mRNA expression of three STs (ST6Gal I, ST3Gal III, and ST3Gal IV) in cervical intraepithelial lesions (CIN). Alterations of these STs mRNA expression were examined in 35 cervix specimens classified as normal, CIN 1, CIN 2 and CIN 3, by semiquantitative reverse transcription-polymerase chain reaction. mRNA expression of the three STs was enhanced in CIN 1, CIN 2 and CIN 3 with respect to normal tissue, with a significant difference of p < 0.001 (Mann-Whitney U test) for all the enzymes. Our results suggest that altered expression of ST3Gal III, ST3Gal IV and ST6Gal I in CIN could play an important role during malignant transformation and could be related with the enhanced sialic acid expression detected in neoplasic tissues.